Assessment of Factors Associated with Breast Self-Examination among Health Extension Workers in West Gojjam Zone, Northwest Ethiopia - Muluken Azage; Gedefaw Abeje; Alemtsehay Mekonnen (International Journal of Breast Cancer)
Background. Early detection of breast cancer using breast self-examination (BSE) plays an important role in decreasing its morbidity and mortality. Objective. To identify factors associated with BSE among health extension workers in Northwest Ethiopia. Methods. Cross-sectional study design was employed from October to November, 2012 in West Gojjam Zone of Amhara region. Simple random sampling technique was used to recruit a total of 390 health extension workers (HEWs). A structured Amharic questionnaire was used to collect the data. Data were entered and analyzed using SPSS statistical package version 16.0. Result. This study found that 37% of HEWs had ever practiced BSE and 14.4% practiced it regularly. The three main reasons for not doing regular BSE were no breast problem (53.2%), not knowing the technique of BSE (30.6%), and not knowing the importance of BSE (21.4%). Discussion with families on BSE and history of breast examination by health professionals were found significantly associated with ever practice of BSE. Conclusion. BSE practice was found low in this study. Having information on the importance of BSE was predictor of BSE practice. Therefore, it is important to give training on BSE techniques and its role on breast cancer prevention for HEWs.